Intermedial Products for Digital Natives: British Theatre-Cinema on Italian Screens - Pennacchia, Maddalena (Intermédialités / Intermediality, 2017)
The concept of intermediality underwent a deep transformation with the digital turn, when the difference between media became entirely virtual and a continuous communication system superseded the discontinuous analogic system. Does intermediality still make sense in the era of post-media? And, in particular, how do digital natives, with their specific cognitive abilities, perceive intermediality? Can we think of literature in terms of a fluid intermedial relation of writing to other media? And does such an approach help when it comes to teaching literature to digital natives? What are the intermedial products that the creative industries are designing specifically for them? Taking Shakespeare as an eminent example of a writer whose work has been adapted to all kinds of media, this article focuses on the phenomenon of British theatre productions that are conceived to be screened live in cinemas all over the world and presents the results of a pilot experiment devised to investigate the reception of one of these productions by a sample audience of Italian teenagers.